Exchange Rate Pass-Through in Sub-Saharan African Economies and its Determinants - Razafimahefa, Ivohasina (IMF Working Papers; Working Paper ;, 2012)
This paper analyzes the exchange rate pass-through to domestic prices and its determinants in sub-Saharan African countries. It finds that the pass-through is incomplete. The pass-through is larger following a depreciation than after an appreciation of the local currency. The average elasticity is estimated at about 0.4. It is lower in countries with more flexible exchange rate regimes and in countries with a higher income. A low inflation environment, a prudent monetary policy, and a sustainable fiscal policy are associated with a lower pass-through. The degree of pass-through has declined in the SSA region since the mid-1990s following marked improvements in macroeconomic and political environments.